DUNIA PENDIDIKAN : Antara Dilema dan Harapan (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
There is no one the nations in the world to be developed without going through theprocess of education builder, and through the process of educational development that is anindicator of a countryâs quality of human resources. The more advanced educational developmentof a country, then the impact on the quality of human resources.Indonesiaâs efforts to become an industrial country should be followed by an increase in thequality of reliable human resources. For that educational institutions should be managedprofessionally to be able to produce the human resources needs and market demand.It gives guidance to us that the development of education is part of the national development.The success of educational development will have broad impact on national development. Thus,the development of education is of national development subsystem.Keywords: World Education, dilemmas and expectations